Thermal physics tutorial with Python simulations / Minjoon Kouh and Taejoon Kouh. - Kouh, Minjoon; Kouh, Taejoon (Series in computational physics., 2023)
This volume provides an accessible introduction to thermal physics with computational approaches that complement the traditional mathematical treatments of classical thermodynamics and statistical mechanics.